If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1) + -2(2x + 3) = 5x + -4 Reorder the terms: 5(-1 + x) + -2(2x + 3) = 5x + -4 (-1 * 5 + x * 5) + -2(2x + 3) = 5x + -4 (-5 + 5x) + -2(2x + 3) = 5x + -4 Reorder the terms: -5 + 5x + -2(3 + 2x) = 5x + -4 -5 + 5x + (3 * -2 + 2x * -2) = 5x + -4 -5 + 5x + (-6 + -4x) = 5x + -4 Reorder the terms: -5 + -6 + 5x + -4x = 5x + -4 Combine like terms: -5 + -6 = -11 -11 + 5x + -4x = 5x + -4 Combine like terms: 5x + -4x = 1x -11 + 1x = 5x + -4 Reorder the terms: -11 + 1x = -4 + 5x Solving -11 + 1x = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -11 + 1x + -5x = -4 + 5x + -5x Combine like terms: 1x + -5x = -4x -11 + -4x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 -11 + -4x = -4 + 0 -11 + -4x = -4 Add '11' to each side of the equation. -11 + 11 + -4x = -4 + 11 Combine like terms: -11 + 11 = 0 0 + -4x = -4 + 11 -4x = -4 + 11 Combine like terms: -4 + 11 = 7 -4x = 7 Divide each side by '-4'. x = -1.75 Simplifying x = -1.75
| 9(3x-1)-5=20x | | 172=125-x | | 5t^2+2=7t | | (2/3x+x)+16=102 | | m-9=1.1 | | 4x+29=2x+15 | | y-62500=0.25x | | -3+3(1+4)=6(-6+3n) | | 165=-y+43 | | 7x-(3x+6)=5x-35 | | 5x^3-5= | | x^2-4.9x+2.1=0 | | y=1/7x+75.5 | | x-62500=0.25(125000) | | 18x-15=-21+12 | | 6x-11=-21+12x | | 4x-16=7x+5 | | -(x-3)=-5+3(3x-4) | | 2x(x-2)-1=4-4x(x+3) | | 5x-250= | | x^5-2x^4+7x^3+22x^2-92x+40=0 | | 9h-(h^2-4h+1)=48-h^2 | | 5x-4=9x+8 | | 100+15x=75+17x | | 3a-5a-20=-6a+12 | | 5016/22= | | -100+4t=-50 | | 3.14=4x-2y | | 5=24/X+6 | | x-34=36-4x | | -3=5/x | | 8-8x-2=57+3x-14 |